Analysis of Factors Influencing Employee Work Status - Wang, Siyan (Transactions on Economics, Business and Management Research, 2024)
This study focuses on an in-depth analysis of the factors affecting employees’ work status, aiming to reveal which key factors significantly influence employees’ job performance and satisfaction in the rapidly changing workplace environment. By examining the specific impacts of the physical and psychological environment of the workplace, as well as the balance between work and life under personal factors on employees’ work status, the study identifies that supportive work environments and positive corporate cultures are core reasons for enhancing employees’ work enthusiasm. Meanwhile, a harmonious balance between personal life and work, along with clear career development, are key to maintaining employees’ positive status. Based on these findings, the study proposes a series of targeted recommendations, including strengthening corporate culture construction, optimizing work environment design, improving career development planning systems, and implementing flexible work arrangements, to provide practical guidance for enterprises to enhance employee work efficiency and well-being. This study not only enriches the theoretical framework of factors affecting employees’ work status but also provides valuable references and insights for corporate human resource management practices.